(Pentamethylcyclopentadienato)rhodium Complexes for Delivery of the Curcumin Anticancer Drug. Issue 12 (16th February 2017) - Markham, Jack; Liang, Jun; Levina, Aviva; Mak, Rachel; Johannessen, Bernt; Kappen, Peter; Glover, Chris J.; Lai, Barry; Vogt, Stefan; Lay, Peter A.
Abstract : [Rh III (*Cp)Cl(X, Y)] n + complexes X, Y = Cl, PTA, n = 0 (2 ); X, Y = en, n = 1 (3, Cl – salt;4, PF6 – salt); X, Y = acac, n = 0 (5 ); X, Y = cur, n = 0 (6 ), where *Cp = pentamethylcyclopentadienato, curH = curcumin; PTA = 1, 3, 5‐triaza‐7‐phosphatricyclo[3.3.1.1]decane; en = 1, 2‐ethanediamine; acac = acetylacetonato = 2, 4‐pentanedionato(1–) were synthesized from [Rh(*Cp)(µ‐Cl)Cl]2 (1 ). While2 –5 were inactive against human epithelial A549 lung‐cancer cells in assays of cytotoxicity, and antimetastatic and proapoptotic behaviors, 6 had a cytotoxic activity similar to that of curH over 72 h, but at 24 h in real‐time cell migration assays, it was less active, showing slow release of curH. All complexes underwent ligand‐exchange reactions with biomolecules and cells within the timeframes of the assays (X‐ray absorption spectroscopy). Intracellular elemental distributions (X‐ray fluorescence microscopy) showed that6 effectively delivered curH to cells, where it was released. Other elemental distributions and caspase activities were consistent with preapoptotic activities. As such, 6 is a promising delivery agent for bioactive ligands, such as curH. However, pure curcumin itself showed a previously unrecognized ability to promote migration of A549 cells at subtoxic concentrations in the presence of endothelial growth factor, which may be a concern for its widespread use as a nutritional supplement and as a potential drug. This aspect warrants further research. Abstract : [Rh III (*Cp)(curcuminato)Cl] (*Cp = pentamethylcyclopentadienato) is readily taken up by the A549 lung‐cancer cell line and enables the slow intracellular release of curcumin that causes cytotoxicity by apoptosis. This makes the complex an effective drug‐delivery system for the poorly bioavailable curcumin drug.